EVALUASI DAMPAK FASILITAS KAWASAN BERIKAT MENGGUNAKAN COST-BENEFIT ANALYSIS - Nurcahyo, Marsanto Adi; Utomo, Rachmad; Murwani, Sri; Aritonang , Yoke Ruminson; Iriansyah, Nur Firman (Unit Penerbitan Politeknik Keuangan Negara STAN, 2025)
This study analyzes the effectiveness of bonded zone facility incentives in generating economic benefits for the country compared to the fiscal costs incurred. Using the Cost-Benefit Analysis method and the Net Present Value (NPV) approach, this research is conducted as a case study on three companies receiving bonded zone facilities, namely PT. A, PT. B, and PT. C. The results show that PT. A have a Benefit-Cost Ratio of 0.238, indicating that the economic benefits generated are still lower than the fiscal costs provided. In contrast, PT. B and PT. C has a Benefit-Cost Ratio of 2.235 and 1.575, demonstrating that this company provides greater economic benefits than the costs incurred by the government. These findings have implications for optimal tax policy, suggesting that fiscal incentives should be more selectively allocated based on long-term economic potential. Therefore, this study recommends periodic evaluations of bonded zone policies to ensure the effectiveness of fiscal incentives, enhance transparency in facility utilization, and design a stricter supervision mechanism. For future research, it is recommended to conduct an analysis of all companies receiving bonded zone facilities to obtain a more comprehensive understanding of the impact of this policy on the national economy.